A4NH researchers contribute evidence around food systems transformation for safe, healthy and sustainable diets to the United Nations Food Systems Summit (UNFSS) process - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The United Nations Food Systems Summit (UNFSS) process, in particular, the national Dialogues helped Member States to develop food systems transformation pathways towards sustainable food systems and solicit expressions of intention to support these pathways from a broad range of stakeholders. A4NH resources, such as the national food systems profiles, an online evidence map on food systems innovations, and numerous peer-reviewed publications, contributed to informing the Dialogues, in addition to specific action areas, solution clusters, and coalitions.